Electro‐Reconstruction‐Induced Strain Regulation and Synergism of Ag‐In‐S toward Highly Efficient CO2 Electrolysis to Formate. (18th March 2022) - Zhang, Jiguang; Fan, Tingting; Huang, Pingping; Lian, Xinyi; Guo, Yuting; Chen, Zhou; Yi, Xiaodong
Abstract: Formate production from direct CO2 electrolysis is economically appealing yet challenging in activity, selectivity, and stability. Herein, sulfur and silver dual‐decorated indium quasi‐core–shell structures with compressive or tensile strain are rationally designed for efficiently electrocatalyzing CO2 to formate. The introduction of Ag and S increases the current density, Faradaic efficiency, and operational stability of formate both in H‐cell and flow cell systems. As a result, the optimized Ag‐In‐S bimetallic catalysts exhibit the FEHCOO − of ≈94.0% with a J HCOO − of more than −560.0 mA cm −2 at ≈−0.951 V RHE in the flow cell system, which far surpasses the undecorated In catalyst. The experimental and theoretical calculations provide a deeper understanding of the role of the interfacial strain between In or In4 Ag9 shell and AgIn2 core in boosting the electrocatalytic CO2 reduction efficiency, in which the formation energy of *OCHO intermediate decreases and the charge transfer rate is accelerated by interface strain. Abstract : The bimetallic quasi‐core–shell Ag‐In‐S catalysts synthesized by in situ electro‐reconstruction exhibits a J HCOO − of more than −560 mA cm −2, and long‐term stability for formate production because the interfacial strain and the synergism effect between Ag, In, and S lead to fast electron transfer rate and the optimized energy barrier on the catalysts surface.